E-Purchasing Implementation Success (e-PIS) framework in construction organizations: an empirical analysis - Deraman, R.; Rahim, F.A.; Mohamed, O.; Othman, M. (Penerbit UKM, 2013)
Studies have shown that e-purchasing saves millions of dollars in transaction, reduces the supplier base, promotes paperless transaction and, increases transparency and accountability. However, a few studies have reported that between 75-85% of e-purchasing projects have failed to achieve the promised results. Currently, studies undertaken to identify critical success factors (CSFs) of epurchasing implementation in various industries is growing. Unfortunately, little headway is made in the direction of the construction industry, leading to lack of understanding and limited research framework. The aims of this paper are to establish a framework of organizational CSFs for e- Purchasing implementation and examine their relationship towards the successful implementation. The study adopts the survey questionnaire approach to collect empirical data. The questionnaire was distributed to the selected construction organizations which adopted an e-Purchasing using purposive sampling method and a total of 123 responses were used for analysis. The results from principle component factor analysis and correlation analysis provide 8 components of organizational CSFs comprises of 52 CSFs item which shows statistical relationship with e-Purchasing implementation success in dimension of project management success and user satisfaction. The result of the study provide a new framework for studies of construction organizational CSFs in e- Purchasing implementation in Malaysian construction organizations context.